Meningkatkan Keterampilan Mencuci Sepatu Melalui Model Explicit Instruction Bagi Anak Tunagrahita Ringan - Intan Budi Ramadhani; Jon Efendi (Jurnal Penelitian Pendidikan Khusus, 2022)
This study is in the background by the problems found on the ground there are two lightly impaired learners who experience problems with a lack of understanding of children in self-building skills to wash shoes. Based on these problems, the study focused on improving shoe washing skills using explicit instruction learning models. This study aims to find out how the process of washing shoes using explicit instruction learning models for children with mild impairment. This research uses a form of qualitative and quantitative approach with the type of method used, namely classroom action research conducted by collaborating with classroom teachers. The data analysis techniques used in this study are collecting data, reducing data and drawing conclusions. The research consists of foue meetings and is carried out in several stages, namely planning, action, observation and reflection. The results obtained in the first cycle of each learner have increased but the value obtained has not reached the minimum limit of KKM while in the second cycle learners have increased and obtained value reaching the KKM limit. The conclusion of shoe washing skills is that learners experience a significant improvement using explicit instruction learning models.